2016
DOI: 10.2298/sarh1608391n
|View full text |Cite
|
Sign up to set email alerts
|

Modified Risdon approach using periangular incision in surgical treatment of subcondylar mandibular fractures

Abstract: In comparison with techniques described in the literature, the main advantages of the modified Risdon approach are the following: no need for facial vessels identification; direct, fast, and safe approach to mandibular angle and subcondylar region; relatively simple surgical technique and good cosmetic result – due to aesthetically placed incision. This approach could be recommended for subcondylar fracture as a simplified and safe procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Following this, an English study discussed this technical variant of the conventional Risdon approach. It is called the high submandibular approach (HSMA) or “Strasbourg approach,” which has sometimes been confused with other perimandibular or periangular approaches 5–7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following this, an English study discussed this technical variant of the conventional Risdon approach. It is called the high submandibular approach (HSMA) or “Strasbourg approach,” which has sometimes been confused with other perimandibular or periangular approaches 5–7…”
mentioning
confidence: 99%
“…It is called the high submandibular approach (HSMA) or "Strasbourg approach," which has sometimes been confused with other perimandibular or periangular approaches. [5][6][7] The main modification, when compared with the conventional submandibular approach, was that the skin incision was higher with a surgical dissection below the superficial musculoaponeurotic system (SMAS), allowing for quick intraoperative identification and preservation of the facial nerve branches; however, there are few scientific publications regarding this approach.…”
mentioning
confidence: 99%
“…Similar studies have shown a rate of facial nerve palsy of 7.5% to 17.2% with the retromandibular approach, 20,24 14% to 33% with the pre-auricular approach, 1,25 and 8% to 16% with the submandibular/Risdon approach. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…Two studies determined the rate of FN injury after an RMTMAP approach, with rates of paralysis ranging from 5% to 16% 20,22 . Lastly, in the study of the modified Risdon approach by Nikolic et al, 19 2 patients (8%) developed transient paralysis that resolved within 6 weeks.…”
Section: Orif Approachesmentioning
confidence: 99%